Measurement of CP violation parameters and polarisation fractions in B0s → J/ψK[bar]*0 decays - Aaij, Roel; Aquines Gutiérrez, Osvaldo; D'Argent, Philippe; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Braun, Svende; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Dordei, Francesca; Esen, Sevda; et al. (Journal of high energy physics, 2015)
The first measurement of CP asymmetries in the decay $$ {B}_s^0\to J/\psi {\overline{\mathrm{K}}}^{\ast }{(892)}^0 $$and an updated measurement of its branching fraction and polarisation fractions are presented. The results are obtained using data corresponding to an integrated luminosity of 3.0 fb−1 of proton-proton collisions recorded with the LHCb detector at centre-of-mass energies of 7 and 8 TeV. Together with constraints from B0 → J/ψ ρ0, the results are used to constrain additional contributions due to penguin diagrams in the CP -violating phase ϕs, measured through Bs0decays to charmonium.